Clinical ethics a practical approach to ethical decisions in clinical medicine - Jonsen, Albert R. (McGraw-Hill Medical, 2010)
"This book is about the ethical issues that clinicians encounter in caring for patients. In order to practice excellent clinical care, clinicians and those studying to become clinicians must understand ethical issues such as informed consent, truth telling, confidentiality, privacy, the distinction between research and clinical care, and end-of-life care. Our audience also includes families and other persons close to patients, who may participate in decisions about their care"--Provided by publisher